2012
DOI: 10.1105/tpc.112.099325
|View full text |Cite
|
Sign up to set email alerts
|

Demethylesterification of the Primary Wall by PECTIN METHYLESTERASE35 Provides Mechanical Support to the Arabidopsis Stem

Abstract: Secondary cell walls, which contain lignin, have traditionally been considered essential for the mechanical strength of the shoot of land plants, whereas pectin, which is a characteristic component of the primary wall, is not considered to be involved in the mechanical support of the plant. Contradicting this conventional knowledge, loss-of-function mutant alleles of Arabidopsis thaliana PECTIN METHYLESTERASE35 (PME35), which encodes a pectin methylesterase, showed a pendant stem phenotype and an increased def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
128
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 41 publications
(56 reference statements)
3
128
1
2
Order By: Relevance
“…A remaining challenge is to precisely determine how alteration of wall composition and organization alters wall mechanical properties in the xxt1 xxt2 mutant, given that recent data have shown that wall stiffness is also decreased in two Arabidopsis cellulose-deficient mutants, prc1-1 and prc1-1/the1 , and that pectin modification, especially pectin demethylation, can likewise alter mechanical strength in Arabidopsis stems (Hongo et al, 2012). xxt1 xxt2 walls are more extensible than Col walls upon treatment with pectindegrading enzymes (Park and Cosgrove, 2012a), further supporting the function of pectins in regulating wall biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…A remaining challenge is to precisely determine how alteration of wall composition and organization alters wall mechanical properties in the xxt1 xxt2 mutant, given that recent data have shown that wall stiffness is also decreased in two Arabidopsis cellulose-deficient mutants, prc1-1 and prc1-1/the1 , and that pectin modification, especially pectin demethylation, can likewise alter mechanical strength in Arabidopsis stems (Hongo et al, 2012). xxt1 xxt2 walls are more extensible than Col walls upon treatment with pectindegrading enzymes (Park and Cosgrove, 2012a), further supporting the function of pectins in regulating wall biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Pectins are major components of the plant primary cell wall and middle lamella and have several functions, including involvement in maintaining plant growth and development, promoting cell-to-cell adhesion, providing structural support in soft tissues, defense responses, and influencing wall porosity and thickness, etc (Ridley et al, 2001;Iwai et al, 2002;Ogawa et al, 2009;Wolf et al, 2009;Hongo et al, 2012). Pectins may be the most complex polysaccharide family in the living world, being composed of as many as 17 different monosaccharides and having more than 20 different linkages (Bonnin et al, 2014).…”
mentioning
confidence: 99%
“…5l). The demethylesterification of HG in the base stem of Arabidopsis can strengthen the support structure (Hongo et al 2012). Thus, we suspected a similar function of partially Me/deesterified HG in the strength of M. lutarioriparius stem.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the signal of less methyl-esterified HG recognized by JIM5 monoclonal antibody shows stronger intensity in the basal cortical than upper cortical of Arabidopsis stem, and the pme35-1 mutant involved in demethylesterification of HG in the basal cortical exhibits a pendant stem phenotype, suggesting that ME (methyl esterification) degree of HG could regulate the mechanical strength of Arabidopsis stem (Hongo et al 2012). The presence or absence of weakly ME-HGs and fucosylated xyloglucans in intervessel pit membranes might contribute to Pierce's disease susceptibility in grapevine (Sun et al 2011).…”
Section: Introductionmentioning
confidence: 99%